Comparison of Hand Crushed and Machine Crushed Coarse Aggregates on Concrete. - Ingabire, Peace (2025)
This research aimed at determining the difference in compressive strength of concrete of the same mix design produced by hand and machine-crushed coarse aggregates and the effect of the two types of coarse aggregates on compressive strength on concrete was investigated. The same source for both machine and hand-crushed coarse aggregates was considered so that the aggregates have the same physical and mechanical properties. Properties of concrete compounds such as water and cement were kept constant and no admixtures were used. Mix design for two types of coarse aggregates with the help of the design of normal concrete mixes by H.C. Erntroy and R.E. Franklins was conducted. Test cubes for fresh concrete were crushed after 7, 21, and 28 days of well-cured and stored conditions according to BS 1881 to obtain the compressive strength. Comparisons on compressive concrete strength were made between concrete made with hand and machine-crushed coarse aggregates and recommendations that suit the conditions at hand.